Neural induction suppresses early expression of the inward-rectifier K+ channel in the ascidian blastomere. - Okamura, Y (1993)
1. Early expression of ion channels following neural induction was examined in isolated, cleavage-arrested blastomeres from the ascidian embryo using a two-electrode voltage clamp. Currents were recorded from the isolated, cleavage-arrested blastomere, a4-2, after treatment with serine protease, subtilisin, which induces neural differentiation as consistently as cell contact. 2. The inward-rectifier K+ current increased at the late gastrula stage shortly after the sensitive period for neural induction both in the induced (protease-treated) and uninduced cells. Ca2+ channels, characteristic of epidermal-type differentiation, and delayed-rectifier K+ channels and differentiated-type Na+ channels, characteristic of neural-type differentiation appeared much later than the inward-rectifier K+ channels, at a time corresponding to the tail bud stage of the intact embryo. 3. When cells were treated with subtilisin during the critical period for neural induction, the increase in the inward-rectifier K+ current from the late gastrula stage to the neurula stage was about three times smaller (3.67 +/- 1.74 nA, mean +/- S.D., n = 14) than in untreated cells (11.25 +/- 3.10 nA, n = 26). The same changes in the inward-rectifier K+ channel were also observed in a4 2 blastomeres which were induced by cell contact with an A4-1 blastomere. However, when cells were treated with subtilisin after the critical period for neural induction, the amplitude of the inward-rectifier K+ current was the same as in untreated cells. Thus the expressed level of the inward-rectifier K+ channel was linked to the determination of neural or epidermal cell types. 4. There was no significant difference in the input capacitance of induced and uninduced cells, indicating that the difference in the amplitude of the inward-rectifier K+ currents derived from a difference in the channel density rather than a difference in cell surface area. 5. The expression of the inward-rectifier K+ channel at the late gastrula stage was sensitive to alpha-amanitin, a highly specific transcription inhibitor. In both induced and uninduced cells, injection of alpha-amanitin at the 32-cell stage reduced the current density of the inward-rectifier K+ channel to about 2 nA/nF, corresponding to 13% of that recorded from uninjected cells. By contrast, the expression of the fast-inactivating-type Na+ current, which transiently increased along with the inward-rectifier K+ channel, was resistant to alpha-amanitin injection. 6. The dose of alpha-amanitin injected was controlled by monitoring co-injected fluorescent dye, fura-2.(ABSTRACT TRUNCATED AT 400 WORDS)